Experimental investigation of brake judder noise - Mohammed, Ghaith Jasim (2014)
Brake judder is a braking induced, forced vibration that typically occurs in vehicles. The judder frequency is directly proportional to the revolution speed of the wheel and therefore also to the velocity of the vehicle. The driver experiences judder as vibrations in the steering wheel, brake pedal and structure floor. Brake judder can be split into two distinct groups – “hot” and “cold” judder, both of which can be classified as a mechanically induced vibration. Until recently research efforts regarding brake judder have been overshadowed by other brake related issues such as brake noise for example squeal and groan. This research studies the cold judder by using brake judder test rig (half vehicle). After applying three different pressures (5 bar, 10 bar, 16 bar) for each speed (420 rpm, 330 rpm,250 rpm and 165 rpm), the results show that at 10 bar and 16 bar give a high vibration amplitude that leads to uncomfortable feeling. The result of non-contact displacement sensors show that the disc thickness variation (DTV), disc surface waviness and side run-out (SRO) combination is the cause of brake judder. After inserting a 3mm thick round rubber between the pad and the caliper the magnitude of vibration atthe axial steering direction for velocity of 250 rpm and 420 rpm, and brake pressure of 16 bar changed from fairly uncomfortable region to little uncomfortable region and the magnitude of vibration of brake pedal changed from uncomfortable region to fairly uncomfortable region.